Motivational predictors of children's involvement in out-of-school activities: An application of a football program - Madsen, E. E.; Krustrup, P.; Hansen, T.; Aggestrup, C. S.; Ntoumanis, N.; Larsen, C. H.; Pfeffer, K.; Ivarsson, A.; Ryom, K.; Larsen, M. N.; Madsen, M.; Madsen, J. E.; et al. (Scandinavian Journal of Medicine & Science in Sports, 2023)
The "11 for Health in Denmark" in-school educational football program has shown to have numerous positive physiological and psychological effects in 10- to 12-year-old schoolchildren. A key part of the successful application of the program, however, has not yet been examined, namely the motivational processes underlying participation and behavioral changes. This study examined such motivational processes (i.e., autonomous motivation, beliefs, and intentions) using the trans-contextual model (TCM) and investigated if the 11 for Health in Denmark program increased intentions to participate in physical activity (PA) outside of school in 10- to 12-year-old schoolchildren. Using a web-based questionnaire, Danish-speaking schoolchildren (N = 276 [boys, 50.4%]; Mage = 10.44, SD = 0.35) from three schools and seven classes completed TCM-based questionnaires at three time-points (weeks 0, 1, and 5) while participating in the 11 for Health in Denmark program. Single-indicator structural equation modeling was performed to examine goodness-of-fit and parameter estimates. A path analysis using maximum likelihood estimation was used to test the direct and indirect effects of the TCM model. The results partly supported a mediation sequence, as we found significant direct effects in eight of 13 motivational variables (ß = -0.25-0.83, p < 0.05), indirect effects in one of nine variables (ß = 0.15, p < 0.01), but no effects with regard to PA behavior. Findings provide evidence for a motivational link between Danish-speaking schoolchildren's autonomous and controlled motivation from in school to out of school, and may inform future interventions promoting motivation and participation in out of school PA.